Extracellular PDI in thrombosis and vascular injury - Jinyu Wang; Philip J. Hogg; Xulin Xu; Chao Fang (Thrombosis Journal)
Abstract Protein disulfide isomerase (PDI) catalyzes the reduction, oxidation, and isomerization of disulfide bonds. Although initially discovered as an endoplasmic reticulum (ER)-residing protein, PDI has been demonstrated to play critical roles on cell surfaces and in the extracellular milieu under different pathophysiological settings. During thrombosis extracellular PDI regulates both platelet activation and coagulation, while during vascular injury PDI modulates proinflammatory neutrophil recruitment and the homeostasis of vascular cells. The identification of PDI substrates using mass spectrometry-based techniques such as mechanism-based kinetic trapping and differential cysteine alkylation has significantly advanced our understanding of the mechanisms whereby extracellular PDI regulates these pathophysiological processes. PDI may reduce or oxidize allosteric disulfide bonds and change the function of adhesive receptors, coagulation-related plasma proteins and signaling molecules that are important during thrombosis and vascular injury responses. The catalytic cysteines of PDI can also be post-translationally modified to enable PDI to transmit redox active species. This review aims to summarize the most recent advances about the roles of extracellular PDI in thrombosis and vascular injury and their mechanisms. With the discovery of novel PDI inhibitors, this body of knowledge will provide novel opportunities to develop strategies for the treatment of thrombotic and vascular diseases.